Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-02-14T21:38:58+01:00
2(3a + b) - 2(a - b) = 6a + 2b - 2a + 2b = 4a + 4b

½(4x - 4) - 2(a - b) = 2x - 2 - 2a + 2b = - 2a + 2b + 2x - 2

x(x - 1) - 3(x² - x) = x² - x - 3x² + 3x = - 2x² + 2x

5a(a - 3) - 3a(a - 5) = 5a² - 15a - 3a² + 15a = 2a²

3x(x + ½y) - 2y(½x - ½) = 3x² + 1½*xy - xy + y = 3x² + ½*xy + y
1 5 1
2010-02-14T21:40:50+01:00
2(3a+b)-2(a-b)
6a+2b-2a+2b=4a+4b


½(4x-4)-2(a-b)
½*4x-1/2*4-2a+2b = 2x-2-2a+2b = -2-2a+2b+2x


x(x-1)-3(x²-x)
x*x-1x-3x²+3x = x²-x-3x²+3x = grupujemy = 3x-x+x²-3x² = 2x-2x²


5a(a-3)-3a(a-5)
5a*a-3*5a-3a*a+5*3a = 5a²-15a-3a²+15a – grupujemy - -15a+15a+5a²-3a² = 2a²


3x(x+½y)-2y(½x-½)
3x*x+1/2y*3x-2y*1/2x+1/2*2y = 3x²+1,5xy-xy+y = 3x²+4xy+y
1 5 1
2010-02-14T23:17:02+01:00
2(3a+b)-2(a-b) = 6a+2b-2a+2b = 4a+4b
½(4x-4)-2(a-b) = 2x-2-2a+2b
x(x-1)-3(x²-x) = x²-x-3x²+3x = -2x²+2x
5a(a-3)-3a(a-5) = 5a²-15a-3a²+15a = 2a²
3x(x+½y)-2y(½x-½) = 3x²+1,5xy-xy+y = 3x²+0,5xy+y